Hypothyroidism Incidence in Polycystic Ovarian Syndrome/ Subfertility - Syeda Khalida Naeem, Mohammad Afzal Khaliq, Zafar Abdul Nabi, Imam Alam, Imam Baksh, (Pakistan Journal of Medical & Health Sciences, 2022)
The association of polycystic ovarian syndrome (PCOS) and hypothyroidism is increasingly being recognised. Both syndromes share some common characteristics. In the patients of these two disorders, sub fertility appears frequently. Background and Objective: Hypothyroidism and PCOS are those syndromes that affects the women of child bearing age.These syndromes leads to subfertility. Risk of subfertility can be prevented in the patients of hypothyroidism by treatment at the onset of the disease. As hypothyroidism occurs more commonly in the patients of PCOS, so it is very important to explain its clinical impact. The objective of this study is to find out how hypothyroidism affects the patients who are suffering from polycystic ovarian syndrome. Study Design: The study design of this article is meta-analysis research. Material and Method: In last two months, we have studied many patients in our clinic.Out of these patients, some were diagnosed as patients of hypothyroidism and there were some patients of PCOS. All patients were females.Data including age and BMI was noted from their record sheets. We also noted the level of different hormones of their body.Venous blood samples were drawn and thyroid volumes was checked. Place and Duration: This study is conducted at Gynae and Obs department of Makran Medical College, Turbat and Teaching Hospital Kech, in the last two years in and outdoor from June 2019 to June 2021. Result: The values of triglycerides, cholesterol, fasting glucose , fasting insulin were significantly higher in the patients of PCOS. Levels of different hormones Including FSH, LH, TSH were also different in affected females as compared to control group.Women suffering from pcos are also unable to conceive.Total thyroid dysfunction was seen in almost 50% patients of pcos. Conclusion: Females who were suffering from hypothyroidism had higher volume of their ovaries and cystic ovaries as well.Meanwhile, females who suffered from pcos had more thyroid related diseases as well.Hypothyroidism changes the level of reproductive hormones in females and makes them unable to conceive (causes subfertility).